Praying for a Miracle Part II: Idiosyncrasies of Spirituality and Its Relations With Religious Expressions in Health - de Freitas, Marta Helena; Leal, Miriam Martins; Nwora, Emmanuel Ifeka (Frontiers in Psychology, 2022)
As a continuation of the previous paper, Praiyng for a Miracle – Part I, published in this dossier, this second paper aims at delving deeper into the same theme, but now from a simultaneously practical and conceptual approach. With that in mind, we revisit three theoretical models based on evidences through which we can understand the role of miracle in hospital settings and assess its impact in health contexts. For each of the models described, we seek to illustrate the possible outcomes of belief in miracle as a modality of religious coping in situations of stress and suffering experienced by patients and caregivers in the face of gloomy diagnoses on coming across the limits of medicine to revert certain illnesses (e.g. child cancer) or biological conditions (e.g. fetal malformation). We posit that the judgement about how such mechanism is healthy or not for each of the people involved (patient, caregiver and/or health professional) depends on the modulation between the conception of miracle adopted by the patient and/or caregiver and the concrete outcomes of the way of responding to the situations that accompany the gravity of the illness or condition. In order to understand better this process of psychological modulation that accompanies belief in miracle, we revisit the concepts of spirituality, religiosity and religion, pointing out the connections and distinctions between them from a phenomenological perspective. We then present a conceptual model that take these connections and distinctions into consideration with the aim of fostering an understanding of miracle, its relations with the diversity of experiences of people who meet in hospital settings (patients, caregivers and health professionals) and their respective impacts on healthcare.